The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.32493/frkm.v1i2.2542
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Pengaruh Current Ratio (Cr), Total Asset Turnover (Tato), Dan Debt to Asset Ratio (Dar) Terhadap Return on Asset (Roa), Serta Dampaknya Terhadap Nilai Perusahaan

Abstract: Tujuan dari penelitian ini adalah untuk mengetahui dan menganalisis pengaruh Current Ratio (CR), Total Asset Turnover (TATO), dan Debt Ratio (DR) terhadap profitabilitas baik secara parsial maupun simultan, serta dampaknya profitabilitas terhadap Nilai Perusahaan. Populasi dalam penelitian ini adalah perusahaan jasa penunjang Migas yang terdaftar di Bursa Efek Indonesia untuk periode 2010-2014. Dengan menggunakan teknik pengambilan sampel (purposive sampling) diperoleh sebanyak 8 perusahaan yang akan dijadikan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1
12

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 0 publications
0
3
1
12
Order By: Relevance
“…These results support the research results (Cindy Sandra, 2021) which finds that a negative DAR is not significant to firm value. However, in contrast to the study results (Widodo, 2018), the Debt to Assets Ratio (DAR) had a significant effect on firm value. Debt is a positive sign for the company.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These results support the research results (Cindy Sandra, 2021) which finds that a negative DAR is not significant to firm value. However, in contrast to the study results (Widodo, 2018), the Debt to Assets Ratio (DAR) had a significant effect on firm value. Debt is a positive sign for the company.…”
Section: Discussioncontrasting
confidence: 99%
“…(Enekwe et al, 2014) suggests that the debt to asset ratio can be used to measure how much a company's assets are financed by debt or how much company debt can affect the management of corporate assets. The study results (Widodo, 2018) found that the Debt to Assets Ratio (DAR) had a positive and significant effect on firm value. Debt is a positive sign for the company.…”
Section: H4: Der (Debt To Equity Ratio) Has a Negative And Significan...mentioning
confidence: 97%
“…According to the research of Pioh et al (2018), the return on assets has a partial impact on company value. In research by Widodo (2019), ROA does not affect the firm value variable and is not significant. As a result, in this study, we use return on assets (ROA) as a proxy for the probability ratio analysis of banking organizations listed on the Indonesia stock exchange.…”
Section: Introductionmentioning
confidence: 75%
“…Semakin besar badan usaha maka semakin mudah bagi badan usaha untuk memperoleh sumber pembiayaan baik internal maupun eksternal, sehingga badan usaha cenderung memiliki lebih banyak sumber pembiayaan untuk mendukung kegiatan operasionalnya (Ina Susianti , 2018). Salah satu saham di Bursa Efek Indonesia adalah badan usaha induk migas, yang terpenting untuk perekonomian nasional dan kelangsungan hidup rakyat, permintaan sumber minyak dan gas bahkan lebih tinggi (Widodo, 2019). Tujuan dari riset ini yaitu untuk mengetahui kinerja laporan keuangan dengan cara menganalisis rasio aktivitas dan likuiditas berdasarkan yang terdaftar di BEI yaitu laporan keuangan PT.…”
Section: Pendahuluanunclassified